Structural Opression of Women in Surat Dari Tini Chen: Siapa Saya: A Feminist Literary Criticism - Putu Ayu Agung Amoretta Putri Marlindra; Edi Dwi Riyanto (Soshum: Jurnal Sosial dan Humaniora, 2021)
Women in a patriarchal system have a close relationship with domestic roles. This study aims to describe the construction of women's roles faced by a woman before becoming a prisoner in a short story entitled Surat dari Tini Chen: Siapa Saya written by Tini (pseudonym), a former convict. This research is descriptive qualitative in nature and has qualitative data taken through library techniques. The approach used in this study is structural story analysis and feminist literary criticism with an intersectionalism approach to explaining social phenomena that become the factor of oppression. The results show that three factors (i.e., education, power relations, and psychology) support the formation of structural oppression on Tini. The economic condition is the estuary that underlies the emergence of the factors.